1988
DOI: 10.1248/cpb.36.4941
|View full text |Cite
|
Sign up to set email alerts
|

Supersaturation mechanism of drugs from solid dispersions with enteric coating agents.

Abstract: The crystallization behavior of drugs from supersaturated solutions containing carboxymethylethylcellulose(CMEC)was investigated to clarify the mechanism of supersaturation phenomena from solid dispersions with enteric coating agents in JP XI 2nd fluid(pH 6.8). Nifedipine,griseofulvin and spironolactone were used as drugs.The rate of crystallization of all drugs was remarkably inhibited by the presence of CMEC.It was found that the inhibition was not due to solubilization of the drugs by CMEC. The crystallizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 2 publications
(1 reference statement)
1
25
0
Order By: Relevance
“…However, the observation that solution levels remain higher than the equilibrium solubility value strongly suggests that the polymers are able to inhibit crystal growth. The inhibition of crystallization and crystal growth by polymers has been observed previously [29][30][31][32][33]. Thus it appears that the system has decreased in concentration to a level where nucleation is no longer spontaneous (i.e.…”
Section: Discussionmentioning
confidence: 71%
“…However, the observation that solution levels remain higher than the equilibrium solubility value strongly suggests that the polymers are able to inhibit crystal growth. The inhibition of crystallization and crystal growth by polymers has been observed previously [29][30][31][32][33]. Thus it appears that the system has decreased in concentration to a level where nucleation is no longer spontaneous (i.e.…”
Section: Discussionmentioning
confidence: 71%
“…Raghavan et al attributed the decreased crystallization rate of hydrocortisone acetate in polymer solutions to attractive forces between the polymer and the drug, e.g., by hydrogen bonding (Raghavan et al 2001). Hasegawa et al (1988) investigated ability of CMEC (carboxymethylethyl cellulose) to inhibit crystallization of nifedipine, griseofulvin and spironolactone from supersaturated solutions. The authors noted that the adsorption of CMEC on the surface of nifedipine crystals was the most important factor in inhibiting crystallization from supersaturated solution.…”
Section: Crystallization Inhibition By Polymeric Additivesmentioning
confidence: 99%
“…However, complete coverage, θ eq ¼ 1, is not considered to be a necessary condition for the complete prevention of crystal growth (Kubota and Mullin 1995). Polymer molecules inhibit the introduction of drug molecules from solution into the crystal lattice by occupying growth sites and thereby acting as a mechanical barrier (Hasegawa et al (1988). Several factors, such as hydrophobicity (Tian et al 2007;Zimmermann et al 2009), electrostatic interaction (Pan et al 2001;Tjipangandjara and Somasundaran 1991), and hydrogen bonding between the adsorbate and the interfacial species (Raghavan et al 2001;Somasundaran and Huang 2000;Somasundaran and Krishnakumar 1997) have been found to contribute to the adsorption process.…”
Section: Nucleationmentioning
confidence: 99%
“…In general, the deposition process of a drug from a supersaturated solution depends on two factors: nucleation and subsequent crystallization (7,8). If the carriers used in the above techniques have a low inhibitory effect on drug crystallization, microparticulate crystals of the drug will precipitate from the supersaturated solution (2,9). However, this drug deposition process varies with the combination of drug and carrier.…”
Section: Introductionmentioning
confidence: 99%